2006
DOI: 10.1002/bjs.5544
|View full text |Cite
|
Sign up to set email alerts
|

Negative stress-coping strategies among novices in surgery correlate with poor virtual laparoscopic performance

Abstract: Ineffective stress-coping strategies correlate with poor virtual laparoscopic performance. The need for effective intraoperative stress-coping strategies is evident.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
53
0
3

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(56 citation statements)
references
References 18 publications
(17 reference statements)
0
53
0
3
Order By: Relevance
“…As a community, there is a powerful reluctance by surgeons to acknowledge the impact of stress, making it difficult to embed change as seen in other industries [35,36]. This is particularly important in light of the evidence linking poor coping strategies with poor surgical performance [14].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…As a community, there is a powerful reluctance by surgeons to acknowledge the impact of stress, making it difficult to embed change as seen in other industries [35,36]. This is particularly important in light of the evidence linking poor coping strategies with poor surgical performance [14].…”
Section: Discussionmentioning
confidence: 98%
“…Previous studies have investigated the effect of stress on the cardiovascular response of surgeons [13] or have demonstrated the effects of negative-coping strategies on surgical skill [14]. Studies that have focused on stress and performance have either relied solely on self-report [15], itself potentially inaccurate due to a reluctance of the surgical community to admit to stress [9], or only on objective measures [16,17], failing to incorporate the important selfperception of stress.…”
Section: Introductionmentioning
confidence: 99%
“…Few studies have demonstrated the adverse reactions of external stress [9,13] and negative stresscoping strategies [5] on surgical performance. Data on internal factors, such as sleep deficits, are conflicting.…”
Section: Discussionmentioning
confidence: 99%
“…On demand, further explanations were provided on the scoring system. In the literature, the first trial on the simulator is often not taken into account because it is believed that its main use is to get the subjects accustomed to the simulation [20,25,[31][32][33]. Nevertheless, we believe it is important to register the first contact with the simulator also since it states the absolute starting point of a trainee and leads to the same well-defined study conditions for all participants and all trials.…”
Section: Learning Curvesmentioning
confidence: 98%